School Readiness for Developing Gifted Curriculum Model in Inclusive Schools - Rochmat Wahab; Adi Suseno; Bayu Pamungkas; A'yunin Akrimni Darojat; Pradita Rizky Wirawan; Gena Diniarti; Mar'atu Husnia Alfi; Intan Tamara Sujana (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2026)
This study examines the readiness of inclusive schools in developing and implementing curriculum services for gifted students, as gifted learners are often underserved within inclusive education systems that primarily focus on students with disabilities. The study aimed to analyze school readiness, curriculum models, supporting factors, and constraints in implementing gifted education within inclusive schools in the Special Region of Yogyakarta, Indonesia. The research employed a quantitative descriptive approach with a survey, complemented by qualitative confirmation through focused discussions to deepen and validate the findings. The participants consisted of 39 respondents, including school principals, curriculum development team members, and special education teachers who were directly involved in curriculum planning and instructional implementation for gifted students. Data were collected using questionnaires and focused discussions, while data analysis employed descriptive statistical techniques, including frequencies and percentages, alongside descriptive qualitative analysis through data reduction, categorization, and cross-validation of findings. The results indicate that schools generally demonstrate positive readiness in supporting gifted education through supportive policies, qualified human resources, access to educational resources, and collaboration among stakeholders. Most respondents acknowledged the importance of specialized curricula for gifted students and reported that current curriculum practices are generally relevant to students’ needs and potential. Schools have also begun implementing differentiated learning, enrichment activities, and collaborative curriculum planning involving principals, teachers, parents, and professionals. However, the findings also reveal several important challenges, including limited teacher understanding of gifted curriculum models, lack of standardized operational guidelines, limited implementation of acceleration programs and individualized education programs, as well as inconsistencies in curriculum flexibility and evaluation practices. Focus discussions further revealed that curriculum implementation often depends on teacher initiative and informal differentiated practices rather than systematic institutional frameworks. Overall, the study highlights the need for stronger policy support, sustainable professional development, curriculum flexibility, and systematic evaluation to ensure effective and equitable educational services for gifted students within inclusive schools.